The Effects of 30% Oxygen Concentration Inhalation on Driving Fatigue and Heart Rate Variability - Byung Chan Min; Kazuyuki Mito; Sang Kon Lee; Seoung Chul Kim; Jeong Han Kim; Seung Hee Hong (Tehnički Glasnik)
This study aimed to evaluate the correlation between heart rate variability and driving fatigue through a physiological approach, examining the effects of oxygen concentrations ranging from normal to high. Driver fatigue, a factor in fatal accidents, has complex causes and varied symptoms. The ambiguity in reporting physiological changes due to mixed terminology such as fatigue and drowsiness prompted this study, which is based on the premise that physiological fatigue originates from the same mechanisms as stress. A driving scenario that induces fatigue was simulated, involving fifteen university student drivers. Experiments were conducted at oxygen concentrations of 21%, 30%, and 40%. Data were collected via an electrocardiogram system and analyzed statistically. Our findings reveal that at a 30% oxygen concentration, drivers showed a significant increase in SDNN and a decrease in LF/HF ratio, indicating enhanced autonomic nervous system stability and reduced sympathetic dominance. This intervention was found to effectively reduce and delay driving fatigue, demonstrating that oxygen supplementation at 30% concentration could notably improve traffic safety by mitigating driver fatigue.